Paid caregivers' experiences of falls prevention and care in China's senior care facilities: A phenomenological study - Luo, Yuan; Ran, Haiye; Deng, Yuqian; Li, Huan; Zhang, Mengxi; Zhao, Liping (Frontiers in Public Health, 2023)
Background：In China, as population aging accelerates, senior care facilities have gradually become a mainstream option. According to the World Health Organization (WHO), the annual rate of falls increases from 30% to 50% in senior care facilities. Older adults who live in senior care facilities are three times more likely to fall than those who live in the community. The quality of care is highly related to the occurrence of falls. Therefore, exploring paid caregivers’ experiences is very important to prevent falls in senior care facilities. Objective: Aim to explore paid caregivers’ experiences of fall prevention and care in China's senior care facilities. Further, we discuss the situation and provide suggestions. Design: A phenomenological study using face-to-face, in-depth, semi-structured interviews. Setting: Four senior care facilities in Changsha, Hunan, China. Participants: 14 paid caregivers in 4 senior care facilities, including nursing assistants and senior nurses. Methods: A purposive sample method was used to select 14 nursing assistants and senior nurses from four different senior care facilities in Changsha from March to April 2022. Everyparticipant was individually to make a face-to-face, in-depth, semi-structured interview. Based on the phenomenological research methodology, the thematic analysis method and Colaizzi analysis method were used for data analysis and theme extraction. Results：Based on interview data, a total of seven themes were distilled: (1) Paid caregivers' professional requirements; (2) Paid caregivers' attitude towards falls; (3) Paid caregivers' fall training and education; (4) Paid caregivers' knowledge about falls; (5) Paid caregivers' fall risk assessment; (6) Paid caregivers' fall prevention; (7) Paid caregivers' fall treatment. Conclusion：In China's senior care facilities, paid caregivers need to be responsible and pay appropriate attention to older adults. First senior nurses and nursing assistants need to enhance communication and cooperation. Secondly, they must learn about deficiencies of fall risk assessment and try their best to improve the capability. Thirdly, they must adopt appropriate education methods to improve fall prevention capability. Finally, the protection of privacy should be taken seriously.